Acute edema blisters in a hereditary angioedema cutaneous attack - Fernández Romero, D. (2008)
Numerous skin diseases are characterised by the presence of blisters. In some of them, blistering is their main manifestation while in others this is an infrequent finding. Most of these diseases are associated with substantial morbidity and some of them can cause death. Thus, an appropriate differential diagnosis and prompt and correct treatment is mandatory. Bullae characteristics like location, spread and itching and mucus membrane affectation help to pinpoint specific diseases. Moreover, accompanying systemic symptoms, previous exposition to drugs, insects or other sick people add to the differential diagnosis1. Acute edema blisters rarely develop in older patients presenting with acute cardiac insufficiency or renal failure, but they have not been described in hereditary angioedema, another very uncommon cause of acute and massive edema formation.